Endocrine Disrupting Chemicals Interfere With Leydig Cell Hormone Pathways During Testicular Descent in Idiopathic Cryptorchidism - Fénichel, Patrick; Chevalier, Nicolas; Lahlou, Najiba; Coquillard, Patrick; Wagner-Mahler, Kathy; Pugeat, Michel; Panaïa-Ferrari, Patricia; Brucker-Davis, Françoise (Frontiers in Endocrinology, 2019)
Cryptorchidism, a frequent genital malformation in male newborn, remains in most cases idiopathic. On the basis of experimental, epidemiological, and clinical data, it has been included in the testicular dysgenesis syndrome and believed to be influenced, together with genetic and anatomic factors, by maternal exposure to endocrine disrupting chemicals (EDCs). Here, we analyze how EDCs may interfere with the control of testicular descent, which is regulated by two Leydig cell hormones, testosterone, and insulin like peptide 3 (INSL3).